An Empirical Analysis on the Mispricing of Initial Public Offerings (IPOs) in Chinese Stock Market(2006-2012) - Li, Ying (2014)
This dissertation provides an empirical analysis on the mispricing of initial public offerings (IPOs) in Chinese stock market and seeks for the factors which leading to the mispricing. A sample of 1130 Chinese IPOs data during the period from 2006 to 2012 are selected including 996 underpriced new shares and 134 overpriced new issues. The total dataset also will be divided into two groups: IPOs underpricing and overpricing, then finding the differences between these two groups.